Labor Supply Effects of a Universal Cash Transfer - Jan Gromadzki (Institute of Labor Economics (IZA), 2023)
I investigate the labor supply effects of the introduction of a large unconditional cash benefit. I exploit the unique design of the child benefit program in Poland to identify the income effects of the monthly transfer in a difference-in-differences design. On average, the marginal propensity to earn out of unearned income was equal to -0.14. For every extra 100 dollars in monthly child benefit transfers households receive, they spend 43 dollars on consumption and save 43 dollars. Additional evidence shows that the program had a positive impact on investments in human capital and home production efficiency.
Keywords: I38; J21; J22; 330; unconditional cash transfer; income effects; labor supply; child benefit; poverty; difference-in-differences